Contraceptive Knowledge and Usage among women famers’ in Yewa Division of Ogun State, Nigeria. - Adebayo, Oyefunke Olayemi (Advances in Social Sciences Research Journal, 2016)
The study assessed contraceptives knowledge and usage among women farmers in Yewa Division of Ogun State. Multistage sampling technique was used to select on hundred and twenty respondents for the study. Both descriptive and inferential statistics were used in analyzing the collected data on contraceptives use, information source, awareness and personal characteristics. Most of the women (70.0%) were age between 30-49years, married (71.7%) having between 6-10 household size. Of all the respondents 82.5% have high level of awareness toward contraceptives. The contraceptive use includes condom, abstinence and pills. There is significant relationship between contraceptive use and age (r= 0.206; P=0.025) of women farmers in the study area. Women farmers’ awareness level was high with low usage of contraceptive. It is therefore recommended that adult literacy programme and sexual education should be encouraged and there should be proper information on the importance of contraceptives.